Foreword - Bakar, Osman (The Other Press, 2023)
Traces of intellectual and spiritual connection between the Persian and the Malay world became prominent in 16th century, through the works of Hamzah Fansuri—a renowned Malay scholar and mystic who is also revered as the father of Malay literature. Hamzah’s contributions may be regarded as an intellectual gateway that connected Southeast Asian Muslims to the rest of the Muslim world. His writings exhibit a command over Arabic and knowledge of Persian language, in addition to his mother tongue, Malay. In his three outstanding treatises: 1) Asrāru’l-‘Ārifīn (The Secrets of The Mystics); 2) Sharābu’l-‘Āshiqīn (The Drink of Lovers); and 3) Al-Muntahī (The Adept), there are numerous references to the writings of Persian poets and thinkers. In between his discussions he often quotes passages and verses from renowned personalities such as Fakhr al-Din Iraqi (d. 1289), Abd al-Rahman Jami (d. 1492) Muhammad Ghazali (d. 1111) Jalal al-Din Rumi (d. 1273), Sa‘di-e Shirazi (d. 1291), and Mahmoud Shabestari (d. 1340). In 2018 the first ever translation of Hamzah Fansuri's works into Persian by the present authors, was published. The translation provides a platform upon which the Persian reader could familiarize himself with Hamzah’s thoughts, and realize the extent of presence of Persian sources in the formation of such literature. This book presents the outcome of a detailed survey of Hamzah’s aforesaid treatises, highlighting the remarkable presence of Persian poetry and prose in his writings. It will also discuss the context in which such passages were used, and how they fit in Hamzah’s worldview and teachings.